EKSISTENSI PEREMPUAN BERCADAR DALAM AKUN INSTAGRAM @KOMUNITAS MUSLIMAH BERCADAR - Ditha Prasanti; Preciosa Alnashava Janitra (Jurnal Dakwah Tabligh, 2021)
When hearing the term veil, it seems to be attached to the identity of Muslim women who incidentally become a cover for their genitals. There is controversy that arises in the community, sticking to the term veil. Women, veils and the media seem to have a connection with each other that forms the identity of veiled women. But in this article, the researcher revealed another interesting thing about a women's community that carries positive activities, called the "Muslim Muslim Community" (KMB) in Indonesia. As the name implies, this community is an association of Muslim women who use veils to cover their nakedness in their appearance. Researchers want to describe the existence of veiled women who are shown through an Instagram account @ komunitasmuslimahbercadar. Researchers use virtual ethnographic research methods because they observe this community in their Instagram accounts, @komunitasmuslimahbercadar. The data collection techniques used were participant observation, interviews, and documentation. The findings in this study indicate that veiled women who are members of the veiled Muslim community show as a community that upholds the value of humanism and anti-terrorism and has a variety of positive movements and actions. The movement included the action of raising funds, sharing free ta'jil, the message of da'wah in the form of cartoon animation aimed at educating the public about veiled women, the KMB movement were containing discussions on Islamic studies in several regions in Indonesia.